Electrochemical performance of hierarchical hollow CoMn2O4 hanospheres in-situ grown on nickel foam as supercapacitor electrode materials - GE Zongyun (Academic Journals Center of Shanghai Normal University, 2021)
Hierarchical hollow nanospheres of cobalt manganese oxide(CoMn2O4) on nickel foam(NF) are facilely synthesized by a hydrothermal method and post heat treatment in air, and further characterized by diffraction of X-rays(XRD), field emission scanning electron microscope (FE-SEM) and X-ray photoelectron spectroscopy(XPS). In a three-electrode system of electrochemical measurement, the areal capacitance of 0.1 Co2+-250 electrode material is as high as 6 184 mF·cm-2 at 5 mA·cm-2. The hybrid supercapacitor assembled by 0.1 Co2+-250 as the positive electrode and commercial activated carbon (AC) as negative electrode presents a maximum energy density of 0.112 mWh·cm-2 at 1.6 mW·cm-2. Even at the power density of 16 mW cm-2, the energy density still reaches 0.064 mWh·cm-2. After 10 000 charge/discharge cycles under the current density of 2 mA·cm-2, the capacitance retains 93% of the initial value. With excellent electrochemical performance and facilely cost-effective synthesis, such hierarchical CoMn2O4 electrode material may hold great promise for high-performance supercapacitor applications.